LINGUAL UNIT EXPRESSING LOCAL WISDOM IN PRESERVING THE VITALITY OF CULTURAL VALUES - LE Pradita, Sumarlam, K Sadhono, M Rohmadi (International Journal of Advanced Science and Technology, 2020)
This study aims to explain the use of the forms and functions of the lingual unit as an expression of local wisdom in preserving the vitality of cultural noble values. Petatah-petitih needs to be disclosed again so that the contents contained therein can be valid throughout the ages, not only apply to the lifetime of Sunan Gunung Jati so that it has vital life and functions. Understand and implement the noble values ​​of culture contained in petatah-petitih Sunan Gunung Jatican contribute positively to the strengthening of the character of the younger generation. This study uses anthropological theoretical characters to study lingual units on cultural values petatah-petitih Sunan Gunung Jati. This study uses a qualitative research paradigm. Data analysis was carried out through two procedures, namely analysis during the data collection process and analysis after data collection. The results showed as follows; first, the forms of lingual units expressing local wisdom include words, phrases, sentences and meanings. Second, the functions of the lingual unit expressing local wisdom include (1) the teachings of life outlook; (2) advice or orders; (3) prohibition.